Questionnaire design: identity strategies in university academics in response to the educational reforms - Zanatta Colín, Elizabeth (2017)
We designed a questionnaire that aims to understand what happens to the identity of the teacher as a guiding element of its educative practice in response to the educational reforms –which have generated a constant change in what is expected from their role. The questionnaire was applied to 228 academics from different disciplines in a state public University with an educational model based on competencies. The data were processed by factor analysis and Cronbach’s Alpha. The results were consistent with the hypothesized factor structure, obtaining an acceptable percentage of variance (43%), which explains four factors of identity strategies: resistant-diffuse, attributed, simulated and assumed. The instrumentreported an adequate level of internal consistency (.94). Therefore, the questionnaire has both construct validity and internal consistency.